IMPROVING STUDENTS’ SPEAKING ABILITY THROUGH REPETITION DRILL - Kartikasari, Eni; Arifin, Zainal; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract:The objective of this research is to know how repetition drill technique improves students’ speaking ability of the 7thgrade students of SMP Negeri 6 Ketapang in academic year 2013/2014. The research was conducted using Classroom Action Research method involving 32 students as the research subjects. The data was collected using oral test within 3 cycles of research. Students’ mean score in the 1st cycle (March 10-11, 2014) is not obtained due to reasons. Students’ mean score in the 2nd cycle (March 17-18, 2014) is 68.75. Students’ mean score in the 3rd cycle (March 24-25, 2014) is 80.08. Students’ mean score in 3rd cycle is bigger than 2nd cycle means that there is significant improvement in students’ speaking ability. In conclusion, this research proved that students speaking ability can be improved through repetition drill technique. Keywords: Improving speaking ability, Repetition Drill Abstrak: Tujuan penelitian ini adalah untuk mengetahui bagaimana teknik pengulangan dapat meningkatkan kemampuan berbicara siswa kelas 7 di SMP Negeri 6 Ketapang pada tahun ajaran 2013/2014. Penelitian telah dilakukan dengan metode Penelitian Tindakan Kelas yang melibatkan 32 siswa sebagai subyek penelitian. Data diperoleh menggunakan tes lisan dalam 3 siklus penelitian. Nilai rata-rata siswa pada siklus pertama (10-11 Maret 2014) tidak diperoleh dikarenakan suatu alasan. Nilai rata-rata siswa pada siklus kedua (17-18 Maret 2014) adalah 68.75. Nilai rata-rata siswa pada siklus ketiga (24-25 Maret 2014) adalah 80.08. Nilai siswa pada siklus ketiga lebih besar daripada siklus kedua yang berarti terdapat peningkatan signifikan dalam kemampuan berbicara siswa. Kesimpulannya, penelitian ini membuktikan bahwa kemampuan berbicara siswa dapat ditingkatkan melalui teknik pengulangan. Kata Kunci: meningkatkan kemampuan berbicara, teknik pengulangan